Government Strategy to Build Public Trust through Digital Communication - Pratama, Angga Dimas (Jujurnal Publisher, 2024)
Digital transformation has changed the government's communication patterns with the public so that a communication strategy is needed that is able to strengthen public trust amidst the increasing flow of information and disinformation. This research aims to analyze the government's strategy in building public trust through digital communication and formulate a conceptual framework that integrates the main factors that form trust. The research uses a literature review method with a qualitative approach through a systematic synthesis of reputable scientific literature obtained from various international databases and analyzed using thematic analysis. The research results show that information transparency, communication interactivity, government responsiveness, and disinformation management are strategic dimensions that complement each other in increasing institutional legitimacy and public trust. This research concludes that the success of government digital communication does not only depend on the use of technology, but also on the quality of communication that is transparent, participatory, responsive and credible, thus providing a conceptual contribution to the development of digital government governance oriented towards strengthening public trust.